Accuracy of image-free navigation in intraoperative leg length change from total hip arthroplasty using evaluations from 2D and 3D measurements - Shine Tone; Masahiro Hasegawa; Yohei Naito; Hiroki Wakabayashi; Akihiro Sudo (BMC Musculoskeletal Disorders, 2021)
Abstract Background Leg length discrepancy is one of the most common problems after total hip arthroplasty (THA). The aim of this study was to investigate the accuracy of image-free navigation in intraoperative leg length change (LLC) using evaluations from anteroposterior radiographs (2D measurement) and 3D bone models using CT data (3D measurement). Methods One hundred THAs with cementless cups and stems were performed using an image-free navigation system in our hospital. We evaluated the accuracy of image-free navigation based on LLC from 2D and 3D measurements. Furthermore, we also investigated error in absolute value and correlations between 2D and 3D measurements in LLC. Results The accuracy of image-free navigation based on 2D measurement was 94% within 5 mm and 76% within 3 mm. The accuracy of image-free navigation based on 3D measurement was 92% within 5 mm and 81% within 3 mm. The error in absolute value in LLC between 2D and 3D measurements was 1.7 ± 1.4 mm (range, 0 to 6 mm). A strong correlation was observed between 2D and 3D measurements in the LLC. Conclusions In the present study, good accuracy of image-free navigation in intraoperative LLC was confirmed for both evaluation methods from 2D and 3D measurements. In addition, the error in absolute value in the LLC between 2D and 3D measurements was very small, and we observed a strong correlation between 2D and 3D measurements. Based on these results, evaluation of LLC from radiographs was considered sufficient if radiographs can be taken accurately.